Lack of association between iron status at birth and growth of preterm infants Ausência de associação entre indicadores de anemia ao nascimento e crescimento de prematuros - Rosely Sichieri; Vania Matos Fonseca; Daniel Hoffman; Nadia Maria F Trugo; Aníbal Sanchez Moura (Universidade de São Paulo, 2006)
OBJECTIVE: To assess the association between iron status at birth and growth of preterm infants. METHODS: Ninety-five premature babies (26 to 36 weeks of gestational age) born from July 2000 to May 2001 in a public hospital in Rio de Janeiro, Southeastern Brazil, were followed up for six months, corrected by gestational age. Iron measurements at birth were available for 82 mothers and 78 children: hemoglobin, hematocrit, mean corpuscular volume and plasma iron. All children received free doses of iron supplement (2 mg/kg/day) during the follow-up period and up to two years of age. Multivariate linear regression analyses with repeated measurements were performed to assess factors associated to linear growth. RESULTS: Growth was more pronounced up to 40 weeks of gestational age, increasing about 1.0 cm/week and then slowing down to 0.75 cm/week. The multivariate analysis showed growth was positively associated with birth weight (0.4 cm/100 g; p<0.001) and negatively associated with gestational age at birth (-0.5 cm/week; p<0.001). There was no association between cord iron and mother iron measurements and growth (p>0.60 for all measures). Only two children had anemia at birth, whereas 43.9% of mothers were anemic (hemoglobin <11 g/dl). Also, there was no correlation between anemia indicators of mothers and children at birth (r<0.15; p>0.20). CONCLUSIONS: Maternal anemia was not associated with anemia in preterm infants and iron status of mothers and children at birth was not associated with short-term growth of preterm infants. OBJETIVO: Avaliar a associação entre indicadores de anemia no nascimento e o crescimento de prematuros. MÉTODOS: Crianças prematuras (26-36 semanas de idade gestacional) (n=95), nascidas de julho de 2000 a maio de 2001, em hospital público do Rio de Janeiro, foram seguidas por seis meses, corrigidos pela idade gestacional. Foram obtidos em 82 mães e 78 crianças os indicadores de anemia: hemoglobina, hematócrito, volume corpuscular médio e ferro plasmático. Os prematuros receberam suplemento de ferro (2 mg/kg/dia) durante o seguimento. Análises de regressão linear multivariadas, com medidas repetidas, avaliaram os fatores associados ao crescimento linear. RESULTADOS: O crescimento dos prematuros foi mais acentuado até as 40 semanas de idade gestacional, com aumento de aproximadamente 1,0cm/semana. Após essa fase, o crescimento foi de 0,75 cm/semana. Na análise multivariada o crescimento associou-se positivamente com o peso ao nascer (0,4 cm/100 g de peso ao nascer; p<0,001) e negativamente com a idade gestacional (-0,5 cm/semana; p<0,001). Não se observou associação entre os indicadores de anemia, tanto da mãe quanto das crianças (p>0,60 para todos indicadores) e o crescimento. Somente duas crianças apresentavam anemia no nascimento, enquanto 43,9% das mães apresentavam anemia (hemoglobina<11 g/dl). Os indicadores de anemia da mãe e da criança no nascimento também não apresentaram correlação importante (r<0,15; p>0,20). CONCLUSÕES: A anemia materna não se associou com a anemia dos prematuros no nascimento e os indicadores de anemia das mães e das crianças não influenciaram o crescimento das crianças nascidas prematuras.